Neural correlates of the Dunning–Kruger effect - Muller, Alana; Sirianni, Lindsey A.; Addante, Richard J. (The European journal of neuroscience, 2021)
The Dunning–Kruger effect (DKE) is a metacognitive phenomenon of illusory superiority in which individuals who perform poorly on a task believe they performed better than others, yet individuals who performed very well believe they under‐performed compared to others. This phenomenon has yet to be directly explored in episodic memory, nor explored for physiological correlates or reaction times. We designed a novel method to elicit the DKE via a test of item recognition while electroencephalography (EEG) was recorded. Throughout the task, participants were asked to estimate the percentile in which they performed compared to others. Results revealed participants in the bottom 25th percentile over‐estimated their percentile, while participants in the top 75th percentile under‐estimated their percentile, exhibiting the classic DKE. Reaction time measures revealed a condition‐by‐group interaction whereby over‐estimators responded faster than under‐estimators when estimating being in the top percentile and responded slower when estimating being in the bottom percentile. Between‐group EEG differences were evident between over‐estimators and under‐estimators during Dunning–Kruger responses, which revealed FN400‐like effects of familiarity supporting differences for over‐estimators, whereas “old‐new” memory event‐related potential effects revealed a late parietal component associated with recollection‐based processing for under‐estimators that was not evident for over‐estimators. Findings suggest over‐ and under‐estimators use differing cognitive processes when assessing their performance, such that under‐estimators may rely on recollection during memory while over‐estimators may draw upon excess familiarity when over‐estimating their performance. Episodic memory thus appears to play a contributory role in metacognitive judgements of illusory superiority. Event‐related potentials (ERPS) were recorded for the Dunning–Kruger effect as subjects made metacognitive judgments about performance on a memory task. Over‐ and under‐estimators exhibited a crossover interaction in response times when believing they did best and worst, respectively. A crossover pattern was also observed for ERPs: LPC signals of recollection were found for under‐estimators, whereas familiarity‐based FN400 effects were evident for over‐estimators and correlated with estimates.